Effect of particle surface treatment on dielectric properties of epoxy-alumina nano-composites - Singh M.; Pandey J.C. (My University, 2025)
Epoxy resin is one of the widely used insulating materials in electrical power apparatus and system. Epoxy alumina nanocomposites are formed by incorporating a few weight percentage of nanometric sized aluminum oxide particles in epoxy matrix. Nanocomposites exhibit superior material properties over conventional microcomposites, and recent literature attributes the properties change to particle-matrix interface. In-depth analysis of particle-matrix interaction is necessary to tailor the material properties of nanocomosites for system specific application. This work investigates the effect of particle surface treatment on particle-matrix interaction zone or an interphase. Dielectric properties measurement are carried out with both kind of (as-received and surface treated) nanofillers to understand the effect of particle surface treatment on interphase. Epoxy (LY556) is used as a base polymer, and hardener (HY951) used as a curing agent. Spherical aluminum oxide filler (average particle size 50 nm) are surface treated with 3-Glycidoxypropyltrimethoxysilane (GPS). Qualitative analysis of nanofiller dispersion in polymer matrix is carried out using Scanning Electron Microscopy (SEM). Experimental results show a significant improvement in dielectric properties (e.g. conductivity, dielectric strength, and permittivity) when particles are surface treated before use. Since the filler dispersion at low filler content (1vol. %) for both types of nanocomposites samples (with as received fillers and surface treated fillers) are equivalent, the improvement in dielectric properties is attributed to enlargement of particle-matrix interaction zone for preprocessed nanofillers. © 2016 IEEE.